Methionine‐ and Choline‐Deficient Diet Enhances Adipose Lipolysis and Leptin Release in aP2‐Cre Fatp4‐Knockout Mice. Issue 22 (12th October 2020) - Cheng, Yuting; Gan‐Schreier, Hongying; Seeßle, Jessica; Staffer, Simone; Tuma‐Kellner, Sabine; Khnykin, Denis; Stremmel, Wolfgang; Merle, Uta; Herrmann, Thomas; Chamulitrat, Walee
Abstract : Scope: Inadequate intake of choline commonly leads to liver diseases. Methionine‐ and choline‐deficient diets (MCDD) induce fatty liver in mice which is partly mediated by triglyceride (TG) lipolysis in white adipose tissues (WATs). Because Fatp4 knockdown has been shown to increase adipocyte lipolysis in vitro, here, the effects of MCDD on WAT lipolysis in aP2 ‐Cre Fatp4‐knockout (Fatp4 A−/− ) mice are determined. Methods and Results: Isolated WATs of Fatp4 A−/− mice exposed to MCD medium show an increase in lipolysis, and the strongest effect is noted on glycerol release from subcutaneous fat. Fatp4 A−/− mice fed with MCDD for 4 weeks show an increase in serum glycerol, TG, and leptin levels associated with the activation of hormone‐sensitive lipase in subcutaneous fat. Chow‐fed Fatp4 A−/− mice also show an increase in serum leptin and very‐low‐density lipoproteins as well as liver phosphatidylcholine and sphingomyelin levels. Both chow‐ and MCDD‐fed Fatp4 A−/− mice show a decrease in serum ketone and WAT sphingomyelin levels which supports a metabolic shift to TG for subsequent WAT lipolysis Conclusions: Adipose Fatp4 deficiency leads to TG lipolysis and leptin release, which are exaggerated by MCDD. The data imply hyperlipidemia risk by a low dietary choline intake and gene mutations that increase adipose TG levels. Abstract : A combination of methionine‐ and choline deficiency with Fatp4 deficiency in white adipose tissues (WAT) leads to a postprandial increase of blood leptin, glycerol, and triglycerides (TG) via a metabolic shift toward TG. This work implies that individuals with gene mutations that lead to TG accumulation in WAT may be at risk of hyperlipidemia when consume low choline diets.